Revisión del uso y aplicación de pavimentos reciclados con asfalto espumado a nivel internacional (2024)
This research discloses the techniques, machinery, regulations and environmental impact of pavement recycling with foamed asphalt at an international level, due to its great importance in the economic development of a country. It is a technique based on creating a base layer by injecting small quantities of water and compressed air to a quantity of hot asphalt inside a chamber with recycled material, increasing its initial volume that allows the elaboration of a high performance foamed base by recycling asphalt materials and stone aggregates that guarantee a lower crack index based on the prolonged efforts due to traffic. In spite of this, it has become a problem due to the lack of knowledge regarding its engineering growth in the application.